How Parallel Most-Favored Nation Clauses in the Television Industry Exclude Competitors and Stifle Innovation - Toth, Bill (Science and Technology Law Review, 2013)
Most-Favored Nation clauses (“MFNs”) are price protections common in many facets of commerce. In their simplest form, a seller guarantees that it will not offer a lower price to any competitor of its “most favored nation.” Several antitrust cases, most notably in the health insurance industry, have been brought against monopolists that use MFNs with the effect of excluding “discount” competitors, some of which have been met with success. This Note posits that MFNs between television distributors and content producers may have the same exclusionary effects, even if no single distributor has monopoly power. Because many “discounters” distribute television content across the Internet, rather than via cable, this Note suggests that the exclusion of discounters in the television industry compounds the exclusionary harms to consumers by not only excluding beneficial business methods, but innovative digital video technologies. Drawing on the discussion of “Parallel Exclusion” in Professor Scott Hemphill and Professor Tim Wu’s recent article in the Yale Law Journal, this Note suggests addressing these challenges by revisiting Judge Posner’s “shared monopoly” approach to antitrust liability and provides support for the prohibition on MFNs in television proposed by Senator Jay Rockefeller in the Consumer Choice in Online Video Act.